Análise da interface da coleta de resíduos sólidos domiciliares e recicláveis com a pandemia da Covid-19 no município de Araraquara (SP) - Morais, Mariana Sedenho de (2022)
Covid-19 changed the way of life of the world's population, affecting developed and underdeveloped countries with different coping capacities. Due to the rapid viral spread, Brazil has accounted for a large number of deaths and Brazilians contaminated by the virus. The main form of contamination occurs through droplets in the nose, mouth, and eyes, and it can remain on inanimate surfaces for up to 9 days. In this context, there is the possibility of the presence of the virus in the materials. The general objective was to analyze the impacts of Covid-19 on the collection of household solid waste (HSW) and recyclable waste (RW) in Araraquara (SP), in the period from March 2020 to April 2022. The methodology consisted of characterization of the study area (step 1), literature review about solid waste management (step 2), monitoring of disease cases, social isolation and vaccination (step 3), and analysis of the interface of HSW and RW collection with Covid-19 (step 4). The main results were: the reduction of regular collection and/or interruption of selective collection at the beginning of the pandemic due to doubts regarding the risk of contamination, with subsequent resumption according to the recommendations; the reduction in the mass collected from HSW and RW, especially in months with higher numbers of cases, by approximately -12.5 and -7.1%, respectively, in relation to PMGIRS; the increase in the use of plastic materials and cardboard by 9.64% and 31.66% due to a greater disposal of single-use packaging and utensils; the influence of social isolation and vaccination of the population in reducing cases of the disease; and a greater number of worker absences in the municipality's cooperative in months with greater numbers of cases, indicating their vulnerability to the disease. The research achieved the proposed objectives, and showed that the pandemic caused a rapid change in the population's lifestyle and behavior, reflecting on the composition and generation of waste. The research achieved the proposed objectives, and showed that the pandemic caused a rapid change in lifestyle and behavior of the population, reflecting in the composition and generation of waste. Thus, this study contains recommendations for the management of HSW and RW, aiming to guide waste management in future pandemic events.